"Neurotic people tend to eat less when disinhibited": The mediating role of food-related cognitive flexibility in restrained eaters. (1st December 2022) - Han, Jinfeng; Zhuang, Kaixiang; Yi, Haijing; Jiang, Yan; Ling, Ying; Fan, Linlin; Liu, Yong; Chen, Hong
Abstract: Objectives: This study aims to reveal the individual differences in Neuroticism and cognitive flexibility among successful restrained eaters (SREs), unsuccessful restrained eaters (UREs), and non-restrained eaters (NREs). Moreover, this study is dedicated to investigating whether certain personality traits and cognitive flexibility could concurrently influence disinhibited eating behaviors among restrained eaters and reveal the pathways through which they interact. Methods: Female participants aged 17 and 24 years (NREs = 23; SREs = 24; UREs = 23) were assessed with body mass index (BMI) and appetite state measurement, the Dutch Eating Behavior Questionnaire (DEBQ), the NEO Five-Factor Inventory (NEO-FFI), and the Positive and Negative Affect Schedule. To measure behavioral and neural responses related to cognitive flexibility, participants were required to complete a food-related switching task, and their brain activities were recorded through the technique of electroencephalography (EEG). Here we analyzed two widely investigated components—the N2 and P3 components that separately relate to conflict monitoring and response inhibition. Results: The behavioral performance of food-related task switching did not show significant between-group differences. However, in comparison to NREs and SREs, UREs elicited larger N2 and lower P3 amplitudes during task switching. In addition, UREs exhibited a lower level of Neuroticism than SREs and NREs. Furthermore, food-related task switching induced N2 amplitude fully mediated the association between Neuroticism and disinhibited eating behavior in restrained eaters controlled for BMI and negative affect. Importantly, when a parallel mediation model with N2 and P3 was built concurrently, N2 was still able to fully mediate the association. Conclusion: According to behavioral and neural evidence, increased N2 amplitude induced by food-related task switching totally mediated the negative association between Neuroticism and disinhibited eating in restrained eaters.